2010
DOI: 10.1021/jm100123x
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the 4-Quinolone-3-carboxylic Acid Motif. 3. Synthesis, Structure−Affinity Relationships, and Pharmacological Characterization of 6-Substituted 4-Quinolone-3-carboxamides as Highly Selective Cannabinoid-2 Receptor Ligands

Abstract: A set of quinolone-3-carboxamides 2 bearing diverse substituents at position 1, 3, and 6 of the bicyclic nucleus was prepared. Except for six compounds exhibiting Ki>100 nM, all the quinolone-3-carboxamides 2 proved to be high affinity CB2 ligands, with Ki values ranging from 73.2 to 0.7 nM and selectivity [SI=Ki(CB1)/Ki(CB2)] varying from >14285 to 1.9, with only 2ah exhibiting a reverse selectivity (SI<1). In the formalin test of peripheral acute and inflammatory pain in mice, 2ae showed analgesic activity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 52 publications
(74 reference statements)
0
59
1
1
Order By: Relevance
“…For example, cannabinoid type-2 receptor agonists have been shown to produce anti-angiogenic and anti-proliferative effects in the treatment of various forms of cancers (Vidinsky et al, 2012), to reduce chronic neuropathic pain (Wilkerson et al, 2012), and to beneficially modulate cytokine levels in immunologically-based disease states (Cabral and Griffin-Thomas, 2009). Since cannabinoid type-2 receptors participate in inflammatory processes via modulation of cytokine release, both agonists (Ehrhart et al, 2005) and newly developed classes of antagonists/inverse agonists (Lunn et al, 2008; Pasquini et al, 2011; Pasquini et al, 2010; Pasquini et al, 2012) have been shown to reduce inflammation and hyperalgesia associated with several disease states. Importantly, four indole quinuclidine compounds examined in this study demonstrate from 5-, to over 30-, fold selectivity for binding to cannabinoid type-2 relative to type-1 receptors (Table 3) (Madadi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cannabinoid type-2 receptor agonists have been shown to produce anti-angiogenic and anti-proliferative effects in the treatment of various forms of cancers (Vidinsky et al, 2012), to reduce chronic neuropathic pain (Wilkerson et al, 2012), and to beneficially modulate cytokine levels in immunologically-based disease states (Cabral and Griffin-Thomas, 2009). Since cannabinoid type-2 receptors participate in inflammatory processes via modulation of cytokine release, both agonists (Ehrhart et al, 2005) and newly developed classes of antagonists/inverse agonists (Lunn et al, 2008; Pasquini et al, 2011; Pasquini et al, 2010; Pasquini et al, 2012) have been shown to reduce inflammation and hyperalgesia associated with several disease states. Importantly, four indole quinuclidine compounds examined in this study demonstrate from 5-, to over 30-, fold selectivity for binding to cannabinoid type-2 relative to type-1 receptors (Table 3) (Madadi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Крім цього, ці спо-луки є потенційними інгібіторами β-секретази (BACE) [13], ацетилхолінестерази [14], тирозин-кінази [15], а також агоністами каннабіноїдних рецепторів СВ1 та СВ2 [16][17][18][19].…”
Section: Issn 2308-8303unclassified
“…Except for six compounds exhibiting K i >100 nM, all the quinolone-3-carboxamides proved to be high-affinity CB 2 ligands, with K i values ranging from 73.2 to 0.7 nM and selectivity (CB 1 /CB 2 ) varying from >14,285 to 1.9. Compound 29 (Figure 5) in particular has very high CB 2 receptor affinity (K i = 0.7 nM) and good selectivity of 14,285-fold for this receptor [70]. Recently, in their continuing effort to explore SAR for quinolones binding at CB receptors, they discovered the 8-methoxy derivative 30 (Figure 5) endowed with the higher affinity and selectivity (CB 2 : K i = 0.6 nM; CB 1 : K i >10,000 nM; selectivity >16,666), which behaved as an inverse agonist [71].…”
Section: Novel Cb2-selective Ligandsmentioning
confidence: 99%